HIV prevention and care‐seeking behaviour among female sex workers in four cities in India, Kenya, Mozambique and South Africa. Issue 10 (23rd August 2016) - Lafort, Yves; Greener, Ross; Roy, Anuradha; Greener, Letitia; Ombidi, Wilkister; Lessitala, Faustino; Haghparast‐Bidgoli, Hassan; Beksinska, Mags; Gichangi, Peter; Reza‐Paul, Sushena; Smit, Jenni A.; Chersich, Matthew; et al.
Abstract: Objective: To identify gaps in the use of HIV prevention and care services and commodities for female sex workers, we conducted a baseline cross‐sectional survey in four cities, in the context of an implementation research project aiming to improve use of sexual and reproductive health services. Methods: Using respondent‐driven sampling, 400 sex workers were recruited in Durban, 308 in Tete, 400 in Mombasa and 458 in Mysore and interviewed face‐to‐face. RDS‐adjusted proportions were estimated by nonparametric bootstrapping and compared across cities using post hoc pairwise comparison. Results: Condom use with last client ranged from 88.3% to 96.8%, ever female condom use from 1.6% to 37.9%, HIV testing within the past 6 months from 40.5% to 70.9%, receiving HIV treatment and care from 35.5% to 92.7%, care seeking for last STI from 74.4% to 87.6% and having had at least 10 contacts with a peer educator in the past year from 5.7% to 98.1%. Many of the differences between cities remained statistically significant ( P < 0.05) after adjusting for differences in FSWs' socio‐demographic characteristics. Conclusion: The use of HIV prevention and care by FSWs is often insufficient and differed greatly between cities. Differences could not be explained by variations in socio‐demographic sex worker characteristics. Models to improve use of condoms and HIV prevention and care services should be tailored to the specific context of each site. Programmes at each site must focus on improving availability and uptake of those services that are currently least used.